Ethics and Legal Keys to Biomedical Research in Spain - Cabanillas Sánchez , Antonio; Zavala, Jorge (The Age of Human Rights Journal, 2014)
This study analyzes the Spanish regulations on Biomedical research, with special reference to the Act of July 3, 2007, inspired by the instruments adopted by the Council of Europe and the European Union as well as in the domestic laws of the United States and the United Kingdom, which are pioneers in the field. This is an advanced law which regulates basic character research and the most controversial issues, both in law and ethical spheres, especially in stem cells research, allowing, with certain limits, the use of embryos, human fetuses, ovocytes and pre-embryos. To complement this approach, the study also analyzes the legal regime applied to clinical trials for drugs and health products.